2018
DOI: 10.1029/2018jd028534
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the ENSO on Winter Aerosol Pollution in the Eastern Region of China

Abstract: The modulation of the El Niño/Southern Oscillation (ENSO) on winter aerosol pollution (WAP) in the eastern region of China (ERC) was investigated from a climatological perspective. The results show that the weakened East Asian winter monsoon during El Niño events has an important influence on increased WAP in ERC, especially over northern China. The enhancement of the East Asian winter monsoon related to La Niña events reduces WAP in northeast, east, and south China but increases it in central and western Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 83 publications
1
30
0
Order By: Relevance
“…It provides very detailed sectoral emission information, which is essential for this study. The inventory is being used by the Coupled Model Intercomparison Project Phase 6 (CMIP6, a main model support for the Inter-governmental Panel on Climate Change Sixth Assessment Report) and many other studies [63][64][65][66][67] .…”
Section: Methodsmentioning
confidence: 99%
“…It provides very detailed sectoral emission information, which is essential for this study. The inventory is being used by the Coupled Model Intercomparison Project Phase 6 (CMIP6, a main model support for the Inter-governmental Panel on Climate Change Sixth Assessment Report) and many other studies [63][64][65][66][67] .…”
Section: Methodsmentioning
confidence: 99%
“…Last but not the least, concurrence of multiple climate drivers and their synergistic climate impacts should be considered. Since many other climate factors such as Eurasian snow cover, ENSO, and PDO also show considerable influence on regional circulation and air pollution in China (Chang et al, 2016;Sun et al, 2018;Zhao et al, 2016;Zhao et al, 2018;Zhang et al, 2019;Zou et al, 2017), more studies with concurrent climate drivers could be conducted for comprehensive understanding of climate change impacts. However, these climate drivers may interact with each other with both synergistic or antagonistic effects .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that climate change plays an important role in generating conducive meteorological conditions for the favorable formation and unfavorable ventilation for air pollution in China and many other regions (Cai et al, 2017;Dawson et al, 2014;Horton et al, 2014;Wang and Chen, 2016). Several possible climate factors have been investigated for their effects on winter haze pollution in China, including: 1) Arctic sea ice Zou et al, 2017); 2) Eurasian snow cover (Yin and Wang, 2018;Zou et al, 2017); 3) El Niño-Southern Oscillation (ENSO; Chang et al, 2016;Sun et al, 2018;Zhao et al, 2018;Zhang et al, 2019); 4) Pacific Decadal Oscillation (PDO; Zhao et al, 2016); and 5) the northwestern Pacific sea surface temperature (SST; Pei et al, 2018). In these studies, researchers mainly focused on the relationships of various climate factors with pollution-related weather conditions such as the intensity of East Asia winter monsoon (EAWM), planetary boundary layer height, precipitation, and circulation patterns that correlated with winter haze pollution in China.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al (2017) attributed the elevation of PM 2.5 from heavy (150-250 µg m −3 ) to severe (> 250 µg m −3 ) pollution to aerosol chemical conversion processes, which dominate the later stages of severe haze pollution. According to chamber studies and ambient measurements, the formation of secondary aerosols and their physical and chemical characterizations are markedly dependent on both temperature (Warren et al, 2009;Clark et al, 2016) and relative humidity (RH;Liu et al, 2011;Nguyen et al, 2011;Sun et al, 2013;. Given the lower temperature and ozone concentrations and higher coal consumption in winter in northern China , heterogeneous reactions related to sulfate and nitrate, rather than photochemical reactions, are considered mostly responsible for the increased PM 2.5 concentrations (Ma et al, 2017).…”
Section: Anomalies Of Winter Mean Large-scale Circulations For Two Tymentioning
confidence: 99%